(untitled) (Czech Journal of International Relations, 1999)
The study documents the author’s thesis on the gradual reduction of the pace of economic growth in advanced countries during the past 25–30 years, outlined in other publications. The essay indicates that these countries are heading towards a materially stationary production of commodities and services, adequately saturating the needs of a numerically stagnating population. The last macro-cycle of GDP in the advanced countries (e.g. the period between the great depression in 1929 and 1933 with a culmination in the mid-1970s) will peter out in several years and will not be replaced by a further great economic cycle. But it will be followed by macro-cycles of other groups of countries so that even those which are most backward at present should catch up with the others before the end of the 21st century when a materially saturo-stationary system of a humanitarian nature (with a priority orientation on spiritual needs) will be created on an all-planetary scale. The essay classifies the majority of individual countries in the world against the background of the development of growth rates for the period between 1960 and 1994, possibly 1993 (altogether differentiated in two to four eras), e.g. for a period sufficiently long to draw certain conclusions about the economic dynamics of this or that country.